Who Learns What in Basic Education? Evidence from Indonesia - Afkar, Rythia (World Bank, Washington, DC, 2019)
Indonesia consistently fares poorly on the international tests like PISA and TIMSS. To help diagnosing the causes of poor learning we track student achievement across 9 years in basic education. We find that 40 percent of students do not learn the basics in the early grades of primary school (recognizing 2-digit numbers by 2nd grade, and ordering 4-digit numbers by 4th grade). The authors also find that schools do not cover the complete Indonesian curriculum. Only few students learn how to calculate the surface area of a triangle by 5th grade, the rules about the order of operations, and to complete exercises embedded in stories. Poor and incomplete coverage of the primary curriculum helps explain the low levels of student achievement authors observed in secondary school. Our analysis also provides directions for future research. We observed a large catching-up effect in learning in 6th grade. A plausible explanation for this pattern is the increased pressure on schools, teachers and students to perform well on the high-stakes national exams. The fact that the system can produce learning once (all) actors are sufficiently motivated, suggests that 1.) performance pressure might help, and 2.) that low levels of teacher’s knowledge and skills are currently not a major binding constraint to learning in Indonesia.